Enhanced electrochemical detection of iodide at a reduced graphene oxide-modified carbon electrode in iodized salts - Jamilan, Mohd Azerulazree; Abdullah, Jaafar; Alang Ahmad, Shahrul Ainliah; Md Noh, Mohd Fairulnizal (Elsevier, 2022)
In this study, enhancement of electrochemical performance of electrochemically reduced graphene oxide (ERGO) on a screen-printed carbon electrode (SPCE) (ERGO/SPCE) coupled with ion-pairing (cetyltrimethylammonium bromide, CTAB) for the determination of iodide in table salt has been described. The electrode modification of ERGO/SPCE was conducted using cyclic voltammetric (CV) scanning in the potential range of 1.3–0.4 V for 50 cycles after the drop-casting of graphene oxide (GO) suspension on the SPCE. It was found that the electro-active surface area of ERGO/SPCE was increased by 1.5-fold compared to the bare SPCE. ERGO/SPCE sensor displays linearity towards iodide in the concentration range from 0.020 to 1.0 mg/L (sensitivity = 5.40 µA(mg/L)−1, R2 = 0.9906) with the limit of detection (LOD) and limit of quantitation (LOQ) of 0.070 mg/L and 0.21 mg/L, respectively. The comparison between polarography and ERGO/SPCE sensor was in good agreement.